2020
DOI: 10.3389/fmars.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Global Catches of Marine Recreational Fisheries

Abstract: Commercial fisheries catches by country are documented since 1950 by the Food and Agriculture Organization (FAO). Unfortunately, this does not hold for marine recreational catches, of which only few, if any, estimates are reported to FAO. We reconstructed preliminary estimates of likely marine recreational catches for 1950-2014, based on independent reconstructions for 125 countries. Our estimates of marine recreational catches that are retained and landed increased globally until the early 1980s, stabilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…However, this is likely an underestimate given that only reported catches are represented in FAO data. Underreported catches include recreational fishery catches (Freire et al 2020), artisanal catches, subsistence catches and illegal catches, bycatch/ discards (Zeller et al 2018), and finally catch used as bait which re-enters aquaculture and fishing as an internal input. By reconstructing catches Pauly and Zeller (2016) found that true catches are likely to be 53% higher than reported data.…”
Section: Aquaculture and Fishing: Marine Outputmentioning
confidence: 99%
“…However, this is likely an underestimate given that only reported catches are represented in FAO data. Underreported catches include recreational fishery catches (Freire et al 2020), artisanal catches, subsistence catches and illegal catches, bycatch/ discards (Zeller et al 2018), and finally catch used as bait which re-enters aquaculture and fishing as an internal input. By reconstructing catches Pauly and Zeller (2016) found that true catches are likely to be 53% higher than reported data.…”
Section: Aquaculture and Fishing: Marine Outputmentioning
confidence: 99%
“…In Brazil, the total number of licences issued to recreational fishers for the year 2013 was 401,550 (Freire & Sumaila, 2019). Estimates of recreational marine and estuarine catches in Brazil increased steadily from about 160 t in 1950 to almost 1500 t in 2014, with the highest catches estimated for the southern region of Brazil, including the states of Santa Catarina and Rio Grande do Sul (Freire et al ., 2014, 2020). Unfortunately, there is no historical information on catches of G. barbus from recreational fishing in the estuarine‐lagoon complex mentioned (Tramandaí River, Mampituba River).…”
Section: Figurementioning
confidence: 99%
“…Some rough global estimates available indicated that recreational catches amounted to about 0.5-11 million tonnes, including only inland fisheries, only marine fisheries or both (Coates 1995;Cooke and Cowx 2004), which are small in relation to commercial catches (FAO 2018). Only recently, catches originating from marine recreational fisheries were estimated in a per country basis using several different approaches depending on local data availability, indicating that around 0.9 million tonnes were extracted from marine waters by recreational fishers in (Freire et al 2020. Even though recreational catches are globally small, they may surpass commercial catches for some species (Gentner and Lowther 2002;Coleman et al 2004;Freire et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, catches originating from marine recreational fisheries were estimated in a per country basis using several different approaches depending on local data availability, indicating that around 0.9 million tonnes were extracted from marine waters by recreational fishers in (Freire et al 2020. Even though recreational catches are globally small, they may surpass commercial catches for some species (Gentner and Lowther 2002;Coleman et al 2004;Freire et al 2020). Global number of anglers is also unknown, but Arlinghaus et al (2020) revised all participation rates available around the globe indicating a global participation rate of 10.6% and increasing up to 42% in countries such as Norway.…”
Section: Introductionmentioning
confidence: 99%